Does headquarter structure follow corporate strategy? An empirical study of antecedents and consequences of changes in the size of corporate headquarters - Kunisch, Sven (Journal of Business Economics and Management, 2017)
Despite the importance that scholars and practicing managers attribute to the organizational design of the corporate headquarters (CHQ), research on changes in CHQ size is lacking. In an attempt to empirically explore the antecedents and potential consequences of such changes, I draw on the contingency and organizational-adaptation perspectives to develop a set of hypotheses for the relationships between corporate-level strategic change (CSC) – defined as changes in the firm’s business portfolio –, changes in the size of the CHQ and firm performance. To test the hypotheses, I analyse data from a comprehensive survey of large public firms in Europe and the US, and data from public sources pertaining to the surveyed firms. While the empirical results lend support to the hypothesized role of CSC, they also reveal differences between related CSC and unrelated CSC. However, I find no support for the expected performance implications. The study contributes to research on the CHQ, corporate-level strategic change, and the relationship between strategy and structure in the contemporary corporation. The findings also inform corporate managers and those involved in advising firms, such as strategy consultants.